Control of ligand binding to heme proteins: The role of the distal histidine - Reinisch, Lou (1982)
We have investigated the effect of the distal histidine on the recombination rates of CO and O2 to sperm whale myoglobin, separated beta chains of normal human hemoglobin and to the beta chains of hemoglobin Zurich. The recombination was measured using flash photolysis from 300 to 40 K, on a time scale of 100 ns to 300 s. Lowering the pH of the solution from 7.0 to S.O, we find a 3 kJ/mol and 1.S kJ/mol decrease in the final barrier for CO binding to myoglobin and the separated chains of human hemoglobin, respectively. The distal histidine, His E 7, is identified as the titratable group by observing no pH dependence in the rates when CO binds to the beta chains of hemoglobin Zurich, a mutant of hemoglobin lacking a distal histidine in the beta chains. We postulate a charge-dipole interaction between the CO and the protonated histidine, since the recombination of the symmetric ligand, O2, is pH independent. The temperature independent energy shift is then used to demonstrate the importance of the final barrier even at 300 K, support the sequential model used and finally to spectulate on the structural contributions to the final barrier for binding. The protein structure is shown to be the major contribution to the final barrier for myoglobin. We then show how the distribution of atomic positions from the X-ray scattering data at 80 K can result in the distribution of activation enthalpies observed between 60 and 160 K. Preliminary studies on the effect of pH on the CO recombination to chloroperoxidase show a reversed effect. The rates increase with increasing pH, unlike myoglobin and beta hemoglobin. However, the pK and energy difference between the protonated and unprotonated states suggest a distal histidine is also being protonated in chloroperoxidase. Submitted by Carolyn Mead (cmead2@illinois.edu) on 2011-06-16T14:58:03Z No. of bitstreams: 1 1982_reinisch.pdf: 2140300 bytes, checksum: f4ce9e27aabe6a22ee6237cf56cd5e90 (MD5) Made available in DSpace on 2011-06-16T14:58:03Z (GMT). No. of bitstreams: 1 ...